Pengembangan LKPD Berbasis Open-Ended Problem Pada Materi Segiempat Kelas VII - Apertha, Fanny Khairul Putri; Zulkardi; Yusup, Muhamad (Mathematics Education Journal, 2018)
This study was intended to produce a learner worksheet (LKPD) with valid and practical based open-ended problems and to determine the potential effects on students' learning outcomes in rectangular materials in grade VII. This research was development research. The subjects of this research were students of class VII.5 junior high school no 18 Palembang Indonesia as many as 30 students. Data collection techniques used in this study were a walkthrough, documentation, interviews, and open-ended test questions. The result of data analysis could be concluded that: (1) this research produced LKPD based open-ended problems invalid and practical rectangular material. (2) LKPD that had been developed had a potential effect on the learning outcomes of learners. Therefore LKPD that had been developed can be used by the students.